Carbon capture, utilization, and storage enhances corporate total factor productivity - Wu, Xiaoqi; Yang, Jianfei (Frontiers in Environmental Science, 2025)
Carbon Capture Utilization and Storage (CCUS) is essential for achieving sustainable development and a strong driving force for improving enterprise total factor productivity (TFP). This paper empirically examines the relationship between CCUS and TFP of enterprises based on the collection and organization of CCUS texts in the annual reports of Chinese listed companies from 2002 to 2022. It is found that CCUS has a significant positive impact on corporate TFP. The conclusion still holds after considering issues such as endogenous problems. Mechanism analysis finds that CCUS improves the external environment of enterprises and enhances the ability to obtain bank loans while at the same time improving enterprises’ innovation ability, which in turn helps promote the TFP of enterprises. Heterogeneity analysis finds that the positive impact of CCUS on enterprise TFP is more prominent in large-scale enterprises, state-owned enterprises, and the eight key emitting industries than in small-scale enterprises, non-state-owned enterprises, and other industries. This investigation innovatively employs a text analysis methodology to measure CCUS, reveals the potential determinants influencing CCUS technology on the TFP, and furnishes a scientific foundation for policy refinement.